The Health Costs of Coal-Fired Power Plants in India - Geoffrey Barrows; Teevrat Garg; Akshaya Jha (Institute of Labor Economics (IZA), 2019)
This paper estimates the effect of coal-fired power plants on infant mortality in India. We find that a one GW increase in coal-fired capacity corresponds to a 14% increase in infant mortality rates in districts near versus far from the plant site. This effect is 2-3 times larger than estimates from the developed world. Our effects are larger for: (1) older plants, (2) plants located in areas with higher baseline levels of pollution, and (3) plants burning domestic rather than imported coal. The environmental benefits from policy aimed at the power sector are thus likely to be substantially higher if targeted at older plants located in more polluted areas tailored to burn domestic rather than imported coal.
Keywords: I15; Q51; Q56; Q48; 330; coal; electricity; India; air pollution; infant mortality; infrastructure